Stereotypes against women in the novel "Raaytu Ramallâh" by Mourid Barghouti; A study of feminism - Maulana, Rahmad; Syarifuddin, Syarifuddin (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
A stereotype is a form of gender inequality that often occurs against women with negative labeling of their characteristics, physique, and actions. This study aims to analyze and describe the stereotyping of female characters in the novel Raaytu Ramallâh by Mourid Barghouti. The author cleverly presented interesting and relevant stories about contemporary social conditions prone to stereotypes against women. This study used a qualitative descriptive method on the object, the novel Raaytu Ramallâh, with a content analysis approach focused on examining its contents. Essential data and information collected and studied in this study were words, phrases and sentences containing elements of racial discrimination's impact in short stories. The data were collected through techniques such as reading, recording, and analyzing documents with a feminist approach as the framework of thinking. The results showed there are six forms of stereotypes against women experienced by the female characters in this novel; first, it is women's nature to immediately get proposed to marry right after graduating from elementary school; second, gender differences between women and men cause negative labeling; third, negative stigma against women's physique, attractiveness; fourth, widows are labelled as "foreigners" and "refugees from afar"; fifth, women fighters are labelled "liars" and given the stigma of "one hundred mothers for one child"; and sixth, women's actions are labelled as "lazy".Keywords : Stereotypes, female characters, feminism